Canine Leptospirosis Outbreak in Japan - Saeki, Jun; Tanaka, Aki (Frontiers in Veterinary Science, 2021)
Canine leptospirosis was suspected in 11 dogs in Osaka Prefecture, Japan and 9 dogs died within a month, from October 12 to November 10, 2017. Eight of the dogs had been taken on walks along the same riverbed and 4 dogs lived in the same town. Logistic regression analysis between a comparative group and the incident cases group showed that the odds of leptospirosis infection was 13.3 times higher (p = 0.044) in the dogs taken on walks along the riverbed than in the dogs not being walked along the riverbed. It is suggesting that these walks had been a risk factor. Microscopic agglutination tests showed that antibody titers against Leptospira interrogans serovar Australis were 1:2,560 and 1:10,240 in 2 dogs. Therefore L. interrogans serovar Australis was suspected to be the causative agent, for which no canine vaccine is available in Japan. These results suggested that L. interrogans serovar Australis can cause local outbreaks. The development of a canine vaccine against various serotypes might help reduce local infections. Leptospirosis is an important infectious disease of dogs and it is also a zoonotic disease.